Implementation of incremental conductance method with direct control - Safari, A.; Mekhilef, Saad (2011)
This paper presents incremental conductance (IncCond) MPPT using direct control method in which duty cycle is adjusted inside the algorithm thus need for use another control loop is eliminated while tracking is done perfectly. The steady state oscillations are reduced and dynamic performance is improved. Design and theoretical study and analysis of the proposed system are provided and its feasibility is investigated in Matlab/Simulink simulations. Eventually results are submitted to evaluate the closed loop system.